Analysis of the introduction of scientific articles published in Brazilian journals with Qualis A2 from the administration area (Research, Society and Development, 2020)
This study aimed to analyze whether the structures of introductions of articles published in scientific journals with Qualis A2 in the Administration area present any logical scheme capable of being followed safely. It used the bibliometric method, with a unit of analysis the introductions of texts published in the last 2018 editions of existing journals, whose qualitative and quantitative data were analyzed and interpreted with the aid of semantic, content and comparative analysis techniques. The results showed that the introductions occupy an average of two pages, start with contextualization, justification / motivation / importance and description of the theme / object, continue with the presentation of the objectives and question-problem and end with the presentation of the structure of the article and referencing of other parts (theoretical framework, methodology and results). The conclusion shows that every introduction has initial, central and final elements. The contribution to the Administration area is to provide a safe structure for writing the introductions for these journals.